Overnight switching from oxcarbazepine to eslicarbazepine acetate: an observational study. (22nd July 2016) - Schmid, E.; Kuchukhidze, G.; Kirschner, M.; Leitinger, M.; Höfler, J.; Rohracher, A.; Kalss, G.; Wendling, A.‐S.; Steinhoff, B. J.; Trinka, E.
Abstract : Objectives: There are clinical situations where it might be appropriate to switch patients from immediate‐release oxcarbazepine (OXC) to eslicarbazepine acetate (ESL). We investigated the effects of transitioning patients overnight from OXC to ESL. Materials and Methods: A retrospective, single‐center study was conducted in which patients with drug‐resistant focal epilepsy on a stable dose of immediate‐release OXC for at least 4 weeks were switched overnight to ESL. Patients were switched because they experienced persistent seizures with OXC but were unable to tolerate increased OXC dosing due to adverse events. Tolerability was assessed using the Adverse Events Profile (AEP), quality of life was assessed using the Quality of Life in Epilepsy Inventory 10 (QOLIE‐10), and alertness was assessed as reaction time using a subtest of the Test Battery for Attention Performance version 2.3. Assessments were performed immediately prior to and 5 days after switching from OXC to ESL (days 0 and 5, respectively). Results: The analysis included 21 patients (12 women, 9 men; mean age 36 years). After switching from OXC to ESL, there were significant improvements in mean scores for AEP ( P <.001), QOLIE‐10 ( P =.001), and alertness ( P <.05). Adverse Events Profile total scores improved for 21/21 (100.0%) patients, QOLIE‐10 total scores improved for 17/21 (81.0%) patients, and alertness scores improved for 16/21 (76.2%) patients. Conclusions: In this short‐term, single‐center study, an overnight switch from twice‐daily OXC to once‐daily ESL in patients with drug‐resistant focal epilepsies resulted in improvements in side effects, quality of life, and alertness.